THE INFLUENCE OF E-SERVICE QUALITY AND CORPORATE IMAGE ON E-WOM AMONG BSI MOBILE USERS IN SURABAYA - Ahmadi, Hafizh Ryan; Ridlwan, Ahmad Ajib; Fikriyah, Khusul; Indrarini, Rachma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
In mid-2023, BSI mobile experienced an error which referred to technical problems in the application. This has resulted in many customers feeling uncomfortable and even frustrated because they rely on this application as the main choice for carrying out banking transactions. This incident received a lot of attention through social media sites such as Twitter. The very broad coverage of e-WOM on social media certainly needs to be paid attention to by the company to give the company a good name. This research aims to determine whether there is an influence of e-service quality and corporate image on e-WOM. The research method used in this research is a quantitative approach with primary data. This data was taken from 120 BSI mobile users in Surabaya. The data collection technique used in this research is a data collection technique using a questionnaire and then tested using partial least squares structured equation modeling (PLS-SEM). The results of this research indicate that e-service quality has an influence on e-WOM and Corporate image influences e-WOM. The practical implication of this study is that companies, in this case BSI Mobile, should focus on improving the quality of the services they offer as well as building and maintaining a positive corporate image in the eyes of consumers.